Investigation of biomolecular dynamics by sensitivity-enhanced 1H–2H CPMAS NMR using matrix-free dynamic nuclear polarization - Thomas Biedenbänder; Aryana Rodgers; Mirjam Schröder; Liliya Vugmeyster; Björn Corzilius (Journal of Magnetic Resonance Open)
Molecular dynamics of functional groups contain valuable information about structural properties and functional activities in biomolecules. NMR spectroscopy is a sensitive tool for the investigation of molecular dynamics over a wide range of timescales and thus may deepen the understanding of the biomolecules of interest. Here, we present an approach to use DNP-enhanced 2H NMR to study dynamics of selectively deuterated methyl groups in insoluble proteins such as amyloid beta (Aβ) fibrils. We adopted and optimized the matrix-free DNP approach by varying the amount of added polarizing agent as well as the rehydration level of model proteins. We show that the DNP enhancement obtained in 1H–2H cross-polarization (CP) MAS spectra may increase the sensitivity for selectively deuterated Aβ fibril samples by more than one order of magnitude, accelerating the collection of spin-lattice relaxation data in the DNP-accessible temperature range between 100 and 150 K by up to 400-fold. However, below the coalescence temperature, which describes the transition from the fast to the slow exchange regime, the experimentally obtained relaxation time constants suffer from a paramagnetic relaxation enhancement effect due to the presence of the polarizing agent. This seems to be a general effect for biomolecules as it is also confirmed for two other protein model systems. Our demonstration opens the possibility to extend the scope of 2H NMR for dynamics measurements to effective concentrations and/or temperatures below what is currently accessible; however, the observed interplay between paramagnetic relaxation and molecular dynamics also emphasizes the necessity for a better understanding of relaxation effects in DNP-enhanced NMR.